The Different Methods of Using Solar Energy - Sabzalian , M (Elsevier, 2024)
This chapter will discuss new developments in photovoltaics leading to new methods of cell manufacturing. Contrary to the conventional cells introduced in the previous chapters, these photovoltaic cells are different novel designs used in solar power plants. The section of this chapter will examine the different methods of constructing a floating photovoltaic power plant on water and discuss its features. Tapping the heat received from the sun will also be discussed despite the subject being a complete departure from this book, which is focused on photovoltaics. (Although this discussion will be brief, volume 2 of this book will go into more depth). © 2024 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.